Participatory assessment of the mixed homegardens, its use and management - Guapucal-Cuasanchir, Miriam; Benavides, Ximena Sthefania; Sinisterra, Kelly Xiomara (Revista de Ciencias Agrícolas, 2019)
The lack of knowledge communities have about species in their mixed homegardens, as well as the little value they give to their uses, led to develop the research that took place in the village of Concepción Alto, a town in the municipality of Pasto, located at 1.09º8`8 "of latitude; -77º30`11" of longitude and with 2520 masl. The purpose was to collect, evaluate and systematize the use and management of the species that make up the homegardens, 10 families as key informants were selected, being necessary to stratify them to determine which stratum had the highest knowledge; a semi-structured interview was applied. Knowledge analysis was carried out using the AKT 5 (Agroecological Knowledge Toolkit) methodology. Among the evaluated variables, the outstanding were the specific use of the species, type of management and coefficient of importance, a statistical analysis (Student t test) complemented with their correlation with the variables: age, education, and the number of sentences. To analyze the information the R statistical software was used. The results indicate that the knowledge between the strata I (µ=94±27), II (µ=127±22) and III (µ=75±13) showed no statistically significant differences (p-value=0.3988 >0.05), meaning that all sections share similar knowledge, obtaining a negative correlation between the variables of age and number of phrases (r = -0.31). About the homegardens´ use highlight medicine, food, fodder, fuelwood, timber, shade and water regulation. The homegarden management is conditioned by the experience, beliefs, and new acquired knowledge. In this sense, mixed homegardens in the village of Conception Alto, are a reservoir of plant biodiversity and knowledge.